A Critical Review on the “Natural Order” of the Morpheme Acquisition: Three major Antithetical Views - Bakti, Hendra; Mada Ali, Syahban (Institut Agama Islam Negeri Parepare, 2023)
One of the most contentious and widely discussed studies in Second language acquisition (SLA) theories is the study of morpheme order, which is then renowned as the natural order. As the study generates a number of supports, this paper critically reviews the studies of natural order and presents three major antithetical views against the existing beliefs: the ignorance of other linguistic phenomena, the claim that accuracy is equal to acquisition, and the fatal flaw of overlooking the influence of L1 on L2.